2007
DOI: 10.1007/s11239-007-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Community-based treatment of venous thromboembolism with a low-molecular-weight heparin and warfarin

Abstract: This multicenter, prospective, open label, observational study evaluated practice patterns of physicians using tinzaparin, a low-molecular-weight heparin (LMWH), and warfarin for the treatment of deep venous thrombosis (DVT) with or without pulmonary embolism (PE). Short-term recurrence of venous thromboembolism (VTE) and safety were also evaluated. Patients with an objective diagnosis of DVT, with or without PE, were invited by their physician to participate in this study. Treatment was given according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The risk of recurrent VTE is nearly 50% in patients inadequately anticoagulated, while a 5% rate of serious adverse events is seen even with appropriate anticoagulation [13,14]. The 2009 Joint Commission, National Quality Forum (NQF) and Centers for Medicare and Medicaid Service address this risk by calling for standards focused on reducing patient harm and developing national guidelines associated with use of anticoagulants [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of recurrent VTE is nearly 50% in patients inadequately anticoagulated, while a 5% rate of serious adverse events is seen even with appropriate anticoagulation [13,14]. The 2009 Joint Commission, National Quality Forum (NQF) and Centers for Medicare and Medicaid Service address this risk by calling for standards focused on reducing patient harm and developing national guidelines associated with use of anticoagulants [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical care pathways for VTE are proven, safe, and cost‐effective . Outpatient DVT treatment delivers significant cost savings and averts unnecessary hospital stays .…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical care pathways for VTE are proven, safe, and cost-effective. [9][10][11][12] Outpatient DVT treatment delivers significant cost savings and averts unnecessary hospital stays. 13,14 A hospital-based program providing outpatient DVT treatment among inner-city patients in New York demonstrated a lower incidence of adverse events and substantial cost savings, but excluded PE patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, cancer (even when metastatic) should not be considered in itself a reason for exclusion from treatment at home 17 . Moreover, Hyers reported that home treatment was more common in suburban and rural areas than in urban settings in a large, multicentric study 18 .…”
Section: Discussionmentioning
confidence: 99%